2013
DOI: 10.1080/02533839.2012.734551
|View full text |Cite
|
Sign up to set email alerts
|

Optimal design base shear forces for reinforced concrete buildings considering seismic reliability and life-cycle costs

Abstract: 2013) Optimal design base shear forces for reinforced concrete buildings considering seismic reliability and life-cycle costs, Journal of the Chinese Institute of Engineers, 36:4, 458-470,The objective of this study is to propose a novel estimation procedure for optimal design base shear forces for reinforced concrete (RC) buildings while considering the seismic reliability and life-cycle costs (LCCs) incurred by life-cycle earthquake events. By simulating life-cycle earthquake events within a specified period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In addition to reliability analysis, the optimal design of RC structures is crucial for saving materials and striking a balance between safety and cost. Previous studies have examined the cost minimization problem of RC frame structures (Chutani and Singh, 2017) and considered seismic reliability and life-cycle costs for RC buildings (Chiu et al, 2013). It is essential to conduct an in-depth study on the optimal design of RC structures incorporating uncertain factors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to reliability analysis, the optimal design of RC structures is crucial for saving materials and striking a balance between safety and cost. Previous studies have examined the cost minimization problem of RC frame structures (Chutani and Singh, 2017) and considered seismic reliability and life-cycle costs for RC buildings (Chiu et al, 2013). It is essential to conduct an in-depth study on the optimal design of RC structures incorporating uncertain factors.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, for an RC residential building structure, designers have frequently encountered the problem of a transverse opening in the plastic hinge region of a beam member due to actual pipeline configuration requirements. Recent studies have been conducted on the behavior of simply supported RC beams with transverse opening (Ame et al, 2020;Amiri et al, 2011;Chiu et al, 2023;Ling et al, 2020), some researchers have also reported the use of FRP to strengthen the transverse opening region (Aksoylu et al, 2020;Morsya and Barima, 2019;Özkılıç et al, 2022). However, very little research on a transverse opening in the plastic hinge region of an RC beam has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of structural health monitoring, a large number of scholars have explored the methods of damage identification, safety assessment, and structural reinforcement of bridge structures (Ou & Li, [5]; Chen & Wu, [6]; Xu et al, [7]; Duzgun et al, [8]; Richwalski et al, [9]). In terms of seismic damage identification, there are model-driven damage identification methods and data-driven damage identification methods (Lagaros, Tsompanakis, Psarropoulos & Georgopoulos, [10]; Vafaei, Adnan, Abd & Ahmad, [11]; Hou, Noori & Amand, [12]; Araújo & Laier, [13]; Chiu et al, [14][15][16]).…”
Section: Introductionmentioning
confidence: 99%